The Efficacy and Tolerability of the Clonidine Transdermal Patch in the Treatment for Children with Tic Disorders: A Prospective, Open, Single-Group, Self-Controlled Study - Song, Pan-Pan; Jiang, Li; Li, Xiu-juan; Hong, Si-Qi; Li, Shuang-Zi; Hu, Yue (Frontiers in Neurology, 2017)
Background: To evaluate the efficacy and tolerability of a clonidine transdermal patch in the treatment of children with tic disorders (TD) and to establish a predictive model for patients. Methods: Forty-one patients who met the inclusion criteria entered into 12 weeks of prospective, open, single-group, self-controlled treatment with a clonidine transdermal patch. The Yale Global Tic Severity Scale (YGTSS) was employed before therapy (baseline) and at 4 weeks, 8 weeks and 12 weeks after therapy. Results: 1) The total effect rates of treatment with a clonidine transdermal patch were 29.27%, 53.66% and 63.41% at 4 weeks, 8 weeks and 12 weeks, respectively. Compared with the baseline, the differences were significant at three different observation periods. 2) Compared to the level of 25% reduction, there were significant decreases in the score-reducing rate of motor tic and total tic severities at 12 weeks. 3) If the disease course was ≤24 months and the motor tic score was <16 at the baseline, there was an effective rate of 100% for treatment with the clonidine transdermal patch. If the disease course was ≤24 months and the motor tic score was >16, there was an effective rate of 57.1%. If the disease course was >24 months and the clinical classification was chronic tic disorders, there was an effective rate of 62.5%. If the disease course was >24 months and the clinical classification was Tourette’s syndrome, 90% of the patients were invalid. 4) The main adverse events were rash, slight dizziness and headache. Conclusions: 1) When patients were pretreated with a D2-dopamine receptor antagonist that was ineffective or not tolerated well, switching to a clonidine transdermal patch treatment was effective and safe. 2) A clonidine transdermal patch could be a first-line medication for mild and moderate TD cases that are characterized by motor tics.